Estudio de factibilidad para el desarrollo de un sistema de información gerencial en la Ferreteria Hermanos Chimbo localizada en el cantón Pueblo Viejo - Cepeda Cepeda, Sandra Mercedes (2021)
Currently it is notable that Management Information Systems are necessary in most companies to be able to meet business objectives as well as decision-making, but there are many companies that do not have a Management Information System that allows facilitating its purchasing and sales processes, which makes the company lose time in terms of service, that is why it is desired to implement a GIS in the hardware store "HERMANOS CHIMBO" located in the Pueblo Viejo canton to improve these processes , the system will be based on the current problem that the company is going through, to know if the implementation of this GIS is feasible or not, an operational, technical and economic feasibility study was carried out. It is intended to develop the GIS in NetBeans IDE 8.2 and the PostgreSQL Database Engine. The SIG will be very useful to improve the Purchasing and Sales processes that are developed in the “HERMANOS CHIMBO” Hardware Store.